2010
DOI: 10.1088/0004-637x/723/2/1607
|View full text |Cite
|
Sign up to set email alerts
|

ASTEROSEISMOLOGY OF RED GIANTS FROM THE FIRST FOUR MONTHS OFKEPLERDATA: GLOBAL OSCILLATION PARAMETERS FOR 800 STARS

Abstract: We have studied solar-like oscillations in ∼ 800 red-giant stars using Kepler long-cadence photometry. The sample includes stars ranging in evolution from the lower part of the red-giant branch to the Helium main sequence. We investigate the relation between the large frequency separation (∆ν) and the frequency of maximum power (ν max ) and show that it is different for red giants than for mainsequence stars, which is consistent with evolutionary models and scaling relations. The distributions of ν max and ∆ν … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
252
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 199 publications
(296 citation statements)
references
References 72 publications
44
252
0
Order By: Relevance
“…The comparison between this figure and Fig. 10 in Huber et al (2010) indicates that predictions from theory are in good agreement with the observed behavior of δ ν 02 in RGB and red clump stars. For main sequence stars, the frequency separation δ ν 01 = (ν n,0 −2 ν n1 +ν n+1,0 )/2 has also been suggested as a good indicator of the evolutionary state (e.g.…”
Section: Diagnostic Power Of Red Giant Oscillation Spectrasupporting
confidence: 80%
See 1 more Smart Citation
“…The comparison between this figure and Fig. 10 in Huber et al (2010) indicates that predictions from theory are in good agreement with the observed behavior of δ ν 02 in RGB and red clump stars. For main sequence stars, the frequency separation δ ν 01 = (ν n,0 −2 ν n1 +ν n+1,0 )/2 has also been suggested as a good indicator of the evolutionary state (e.g.…”
Section: Diagnostic Power Of Red Giant Oscillation Spectrasupporting
confidence: 80%
“…observational works based on CoRoT and Kepler satellite data Huber et al, 2010;Mosser et al, 2010;Carrier et al, 2010). In the domain of validity of the asymptotic approximation for pressure modes, the spectrum of p modes can be described by (e.g.…”
Section: Diagnostic Power Of Red Giant Oscillation Spectramentioning
confidence: 99%
“…The star we study here (KIC 12008916) exhibits a very high SNR (Corsaro et al 2015) for the best modes of oscillation (> 250), but detections of individual oscillations are possible at much lower SNR (typically 8). In the absence of instrumental noise (including shot noise), the SNR of the pulsation spectrum is typically determined by the properties of the star (for pulsations, see Huber et al 2010 and background see Kallinger et al 2014). Instrumental noise is somewhat specific to each space mission but is in general a function of stellar magnitude, so that brighter stars have lower instrumental noise and hence higher SNR.…”
Section: The Power Spectrummentioning
confidence: 99%
“…We can compare our identification to the ε-values found in large samples of red giant stars, observed with the Kepler space telescope (e.g. Huber et al 2010;Corsaro et al 2012b). For these stars, we have a solid mode identification from uninterrupted data.…”
Section: Solar-like Oscillations In γ Pscmentioning
confidence: 84%